Joint obtaining of 2,5-diethyl-3,4-dihydro-2H-pyran-2- methanol and sodium salt of 2,5-diethyl-3,4-dihydro-2Hpyran- 2-carboxylic acid via Cannizzaro reaction - Karpyak, Natalya; Marshalok, Galyna; Kovalskyi, Yaroslav; Fedevych, Maria (Publishing House of Lviv Polytechnic National University, 2009)
Kinetic regularities of joint obtaining of 2,5-diethyl-3,4-dihydro-2H-pyran-2-methanol and sodiumsalt of 2,5-diethyl-3,4-dihydro-2H-pyran-2-carboxylic acid have been investigated.Optimal synthesis conditions have been established and physico-chemical characteristics of the main products have been determined. Досліджено кінетичні закономірності процесу сумісного одержання 2,5-діетил-3,4-дигідро-2Н-піран-2-метанолу та Na солі 2,5-дієтил-3,4-дигідро-2Н-піран-2-карбонової кислоти. На основі отриманих результатів встановлено оптимальні умови синтезу цільових продуктів та встановлені їх фізико-хімічні характеристики.
Сумісне одержання 2,5-діетил-3,4-дигідро-2Н-піран-2-метанолу та натрієвої солі 2,5-дієтил-3,4-дигідро-2Н-піран-2-карбонової кислоти за реакцією Канніццаро
Keywords: a-alkylacrolein dimers; derivatives of a-alkylacrolein dimers; Cannizzaro reaction; димери α-алкілакролеїнів; похідні димерів α-алкілакролеїнів; реакція Канніццаро